2010
DOI: 10.1097/tp.0b013e3181c342fd
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Binding Cassette Subfamily B Member 1 Polymorphisms Do Not Determine Cyclosporin Exposure, Acute Rejection or Nephrotoxicity After Heart Transplantation

Abstract: The association of ABCB1 12/1236, 21/2677, and 26/3435 CC/GG/CC haplotype with increased CsA dose- and weight-adjusted CsA trough concentrations in this group of adult white heart transplant recipients was not consistent over time and had no effect on the incidence of acute rejection or on the development of renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…35 Consistent with these observations, the impact of these genetic variants on the pharmacokinetics of calcineurin inhibitors has been variable in clinical studies. 36 -38 Finally, consistent with our results, other studies in heart transplant recipients have found no association between ABCB1 G2677T and/or C3435T and post-heart transplant renal dysfunction, 13,31,38 indicating that these two genetic polymorphisms are not major modulators of calcineurin inhibitorinduced nephrotoxicity.…”
Section: Discussionsupporting
confidence: 94%
“…35 Consistent with these observations, the impact of these genetic variants on the pharmacokinetics of calcineurin inhibitors has been variable in clinical studies. 36 -38 Finally, consistent with our results, other studies in heart transplant recipients have found no association between ABCB1 G2677T and/or C3435T and post-heart transplant renal dysfunction, 13,31,38 indicating that these two genetic polymorphisms are not major modulators of calcineurin inhibitorinduced nephrotoxicity.…”
Section: Discussionsupporting
confidence: 94%
“…All changes of the plasma concentrations appeared to be clinically not relevant. The results from this meta-analysis are essentially supported by further studies in renal or heart transplant recipients (Taegtmeyer et al, 2010;Staatz et al, 2010;Bouamar et al, 2011;Singh et al, 2011). However, most important are physiological factors and co-medication, that is, the body weight was identified as the most important covariate and explained 35% of the random interindividual variability in cyclosporine clearance.…”
Section: Impact On Drug Bioavailabilitysupporting
confidence: 58%
“…72 A recent retrospective single-center analysis including 294 heart transplant recipients treated with CsA also found no association between the ABCB1 1236C.T, 2677G.T/A, and 3435C.T SNPs or ABCB1 haplotype and renal function 1 year after transplantation. 73 With regard to the effect of CYP3A5 genotype on the incidence of renal dysfunction after nonrenal transplantation, even fewer data are available. Recently, Fukudo et al 74 studied 60 adult liver transplant recipients who received Tac-based immunosuppression.…”
Section: Cni-related Nephrotoxicity After Nonrenal Transplantationmentioning
confidence: 99%